Inflammation in acute heart failure - Garofalo, Manuel; Corso, Rossana; Tomasoni, Daniela; Adamo, Marianna; Lombardi, Carlo M.; Inciardi, Riccardo M.; Gussago, Cristina; Di Mario, Carlo; Metra, Marco; Pagnesi, Matteo (Frontiers in Cardiovascular Medicine, 2023)
Acute heart failure (AHF) represents a common clinical scenario that requires prompt evaluation and therapy and that is characterized by a high risk of mortality or subsequent rehospitalizations. The pathophysiology leading to AHF decompensation is still not fully understood. Significant activation of inflammatory pathways has been identified in patients with AHF, particularly in its most severe forms, and it has been hypothesized that systemic inflammation has a role in AHF pathogenesis. Several inflammatory mediators and cytokines, such as high sensitivity C-reactive protein, tumor necrosis factor-α, interleukin-6, interleukin-1, soluble suppression of tumorigenicity 2 and galectin-3, have been shown to play a role in the pathogenesis, development and worsening of this condition with an independent prediction of adverse outcomes. This manuscript reviews the prevalence and prognostic value of systemic inflammation in AHF, as well as the potential role of anti-inflammatory therapies, focusing on available evidence from clinical trials and ongoing studies.